Antecedents and components of burnout among Hungarian teachers in a cross-sectional study: Development of the Burnout Antecedents and Components Questionnaire - Réka Szigeti; Noémi Balázs; Róbert Urbán (Acta Psychologica, 2023)
Background: Studies have focused more on the outcome than on the antecedents of burnout. We aimed to develop a new measurement tool for burnout, including the antecedents and different components drawing from theories of the developmental aspect of burnout. Methods: In this cross-sectional study we tested the Burnout Antecedents and Components Questionnaire on a convenience sample of teachers (n = 618, 83.9 % women; mean age 44.52 years). We used confirmatory factor analyses to test our measurement model. We examined the concurrent validity with the Maslach Burnout Inventory. We also tested construct validity with depression, overcommitment, demographic characteristics and work-related factors. Results: The confirmatory factor analyses supported our measurement model with seven primary factors (need to prove oneself, overload of tasks, neglecting one's needs, conflict between values, interpersonal conflicts, passivity, and emotional drain) and three second-order factors (excessive effort, conflict, and total depletion). The covariates in the Maslach Burnout Inventory showed that emotional exhaustion had a strong relationship with the first- and second-order factors. Overcommitment showed a stronger relationship with factors at the beginning whereas depression showed a stronger relationship with factors at the end of the process. Demographic characteristics and work-related factors did not show strong associations. Conclusions: The Burnout Antecedents and Components Questionnaire is a promising measurement tool with good convergent validity. Future research should further validate our questionnaire for burnout research, prevention, and screening. It adds a new dimension to the measurement of burnout. The approach involving the antecedents in measuring burnout among teachers can guide future research and tailored prevention programs.